Polymer Blends and Nanocomposite Materials Based on Polymethyl Methacrylate (PMMA) for Bone Regeneration and Repair: Characterization and Preparation - Timimi, Zahra; J Tammemi , Zeina (Journal of Sustainable Materials Processing and Management, 2022)
As the population ages, so does the demand for bone loss treatments. The main components of these medicines must be able to endure longer and perform more effectively. Bone cement made of poly (methyl methacrylate) (PMMA), which is often used in damaged bone replacement surgery, is a vital biological material. As a result, the impact of additional nanoparticles such as zirconium dioxide (Zr02) and magnesium oxide (MgO) on polymer binary blends (Acrylic bone cement: 15% PMMA) for a bone scaffold was studied in this research. ZrO2 and MgO nanoparticles were introduced in various weights present to the polymer mix matrix (Zero, 0.5, 1, 1.5, 2). Mechanical characteristics such as tensile strength and Young’s modulus were evaluated for all of the prepared samples. The chemical bonding of nanoparticles and synthetic binary polymeric mix composites was evaluated using FTIR spectroscopy. The tensile strength and Young’s modulus of a binary polymeric blend reinforced with (1.5wt% ZrO2, and 1wt% MgO) both dramatically increased. SEM scanning electron microscopy was used to examine the surface morphology of the fracture surface of tensile specimens. SEM scans demonstrated that nanoparticles (ZrO2 and MgO) were distributed uniformly throughout the polymeric mix matrix.